Pilgrims in the poetry of Abi Ishaq al-Alberti (d 460 AH) An analytical study - Abdel Reda Abdel Saheb , Esra (Journal of College of Education, 2020)
The subject of the research, as indicated by its title (Pilgrims in the Poetry of the Iberian), by which we mean looking at all the techniques adopted by the poet to seek an opinion or to refute an idea in an attempt to persuade the reader or the recipient of what simplifies it or to compel him to submit to what he offers.The pilgrims - in fact - depend on studying the method and method adopted by the speaker to change the beliefs of the recipient and convince him of the subject to be conveyed to him, such as signs, phrases and arguments, in our communication with the other.In the research methodology, we adopted the objective study dividing the work into two topics:The first topic: It is the theoretical aspect, which is familiar with the concepts of pilgrims, and their techniques.As for the second topic, the applied aspect, it includes the poetry of the Hajji discourse and falls into two axes:The first: includes the language and style adopted by the producer of the text in his speech form.As for the second: it includes the picture that the poet drew in his speech as he argued and persuaded the other, then we mentioned a number of results that we reached.perfection in this research, but I have made an effort - as much as I can - to find out the texts of the argument and evidence and then analyze it.